نثار عزیز بٹ کے مثالیت پسند نسوانی کرداروں کا تجزیاتی مطالعہ: An Analytical Study of Idealistic Female Characters in the Works of Nisar Aziz Butt (Research Journal Tahqeeqat, 2025)
This paper presents a critical analysis of the idealistic female characters in the novels of Pakistani Urdu writer Nisar Aziz Butt, with particular focus on her first three works—Nagri Nagri Phira Musafir, Nay Chiragay Nay Gulay, and Karwan-e-Wujood. It argues that the pursuit of an unattainable ideal is a central and defining theme in Butt’s fiction, as reflected in protagonists such as Afgar, Jamal Afroz and Samar Saleh, who are portrayed as complex, often melancholic individuals driven by an intense inner quest for meaning beyond their social and emotional realities. Their uncompromising idealism leads them to reject conventional choices such as marriage and material comfort, resulting in psychological turmoil, alienation, and tragic solitude. Set against broader socio-political contexts, including the aftermath of the Partition of India, these characters also reflect Butt’s deep engagement with Western and Russian literary traditions, particularly Tolstoyan philosophy and existential thought. The study concludes that Butt’s heroines, frequently overshadowing male characters, emerge as powerfully constructed archetypes whose tragic grandeur lies in their unwavering—and ultimately self-destructive—commitment to their ideals.